Analisis Perjanjian Diatas Materai Dalam Kasus Duel Pertarungan - M Auqof; Abdul wahid (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The practice of dueling with serious risks and risking the security of the parties concerned often involves a signed agreement. So, in the case of a duel, the stamped agreement used can give rise to a number of legal and ethical problems.This research uses a normative juridical approach which focuses on legal analysis and interpretation through the study of written legal materials. The research results show that although agreements on stamp duty can fulfill certain legal requirements, their relevance in the context of combat duels is highly questionable. Security, justice, and Compliance with modern social norms should take priority in evaluating and responding to harmful practices such as duel fighting.